New strategies in sepsis diagnosis - Pieteris, Linas; Bakšytė, Giedrė; Česnaitis, Tadas; Vitkauskienė, Astra; Macas, Andrius (Acta medica Lituanica, 2012)
Successful treatment of sepsis begins from early diagnosis and prognosis. In last decades the number of sepsis cases is growing, so establishing early diagnosis of sepsis as well as effectiveness of treatment are very significant. That is why development of new diagnostic sepsis markers is important. In this review we evaluated a new sepsis marker Presepsin (sCD14) and compared it to other markers: Procalcitonin (PCT), C-reactive protein (CRP) and Interleukine-6 (IL-6).
Keywords: presepsin; sCD14; sepsis diagnosis; sepsis prognosis; CRP; PCT; IL-6